2023
DOI: 10.1007/s12072-023-10603-z
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor inhibition by molecular-targeted agents mitigates immunosuppressive tissue microenvironment in hepatocellular carcinoma

Hiroyuki Suzuki,
Hideki Iwamoto,
Toshimitsu Tanaka
et al.

Abstract: Background & aims Combination immunotherapy refers to the use of immune checkpoint inhibitors (ICI) and molecular-targeted agents (MTA), which have recently been approved for the treatment of advanced hepatocellular carcinoma (HCC). Owing to its relatively low antitumor effect (up to 30%), sequential therapy following ICIs treatment is required in patients with HCC. This study aimed to determine the impact of MTAs on the tumor immune microenvironment (TIME). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Recently, FGFR5 lacking the intracellular tyrosine kinase domain, but serves to regulate excessive activation of the pathway by the ligand has been identified (Yue et al 2021). Activation of the receptors by ligand; Fibroblast growth factor (FGF) binding leads to the activation of a series of cascades, which are regulatory to cell growth, differentiation, migration and survival in cells derived from mesoderm and neuroectoderm (Haugsten et al 2010;Qin et al 2019;Suzuki et al 2023). Aberrant expression of FGFRs has been reported to be involved in carcinogenesis and progression of selected human neoplasia including breast cancer (Blanckaert et al 1998;Haugsten et al 2010;Kuroso et al 2010;Helsten et al 2016;Qin et al 2019;Wu et al 2022;Bou Zerdan et al 2023), with FGFR2 suggested as a breast cancer susceptibility gene (Meyer et al 2008;Sun et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, FGFR5 lacking the intracellular tyrosine kinase domain, but serves to regulate excessive activation of the pathway by the ligand has been identified (Yue et al 2021). Activation of the receptors by ligand; Fibroblast growth factor (FGF) binding leads to the activation of a series of cascades, which are regulatory to cell growth, differentiation, migration and survival in cells derived from mesoderm and neuroectoderm (Haugsten et al 2010;Qin et al 2019;Suzuki et al 2023). Aberrant expression of FGFRs has been reported to be involved in carcinogenesis and progression of selected human neoplasia including breast cancer (Blanckaert et al 1998;Haugsten et al 2010;Kuroso et al 2010;Helsten et al 2016;Qin et al 2019;Wu et al 2022;Bou Zerdan et al 2023), with FGFR2 suggested as a breast cancer susceptibility gene (Meyer et al 2008;Sun et al 2012).…”
Section: Introductionmentioning
confidence: 99%